Comparison of two methods for sialometry: weighing and volume techniques - Sacon, Murillo Brunheroto; Esteves, Camilla Vieira; Florezi, Giovanna Piacenza; Gonçalves, Andressa Ferreira; Pannuti, Cláudio Mendes; Lemos Junior, Celso Augusto (Clinical and Laboratorial Research in Dentistry, 2018)
The composition of saliva is essential for the oral cavity homeostasis, therefore, the decrease in salivary flow leads to consequences, such as an increase of dental caries, dry mouth and lips, dysgeusia, dysphagia, gingivitis, halitosis, mastication problems, oral mucositis, oral pharyngeal candidiasis, sleeping and speaking difficulties and traumatic oral lesions. The objective of this study was to evaluate the efficacy of the sialometry technique by weighing in comparison to the sialometry technique by volume. Fifty patients without previous complaint of xerostomia and/or hyposalivation were selected at the Oral Medicine Clinic, Dentistry School, University of São Paulo, Brazil. All samples were collected between 9 am and 10 am and the whole saliva was collect stimulated and unstimulated. Six cotton rolls were prepared, divided into three pairs and placed in different universal dispensers of a random brand, they were weighed in a previously calibrated analytical balance (FA-2104N CELTAC). The sialometry test was performed in three steps: unstimulated salivary flow, salivary flow with stimulation of 1% citric acid solution and stimulation of 1% citric acid solution every 30 seconds. The results of the weighing method were compared to the standard method. There was no significant statistical difference between the two types of collection and 100% of the participants expressed their preference for the weighing method.